Review of Research Progress on Aluminum-Steel Dissimilar Welding - M., Ishak; L. H., Shah (Taylor & Francis, 2014)
This paper presents a review of research progress on aluminiumâsteel dissimilar welding. Current issues and recent developments in improving the intermetallic compound layer of weld joint are critically assessed. Several welding factors that improve joint quality, such as welding method, weld and material preparations, as well as welding parameters, are also discussed. This study also examines recent developments in hybrid welding techniques and proposes a preheating method to enhance the weld joints of aluminiumâsteel dissimilar welding